Correlation of Toluene Safe Concentration, Malondialdehyde and Glutathione Levels in Osowilangun Shoe Home Industry Workers - Emilia Yoanita Rachma1 , Abdul Rohim Tualeka2 , Juliana Jalaludin3 , Syamsiar S Russeng4 , Pudji Rah (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Toluene is the main organic solvent found in adhesives used for shoe production inOsowilangun Shoes Home Industry. Exposure to toluene that exceeds the threshold value can cause theemergence of free radicals which eventually increase the concentration of malondialdehyde and reduce theconcentration of glutathione in the body. The purpose of this research is to study the safe concentration oftoluene with levels of malondialdehyde and glutathione in Osowilangun shoe home industry workers.Methods: This is an observational study using cross sectional design and quantitative approaches. Thereare 25 people were taken as sample by using accidental sampling technique. Data analysis used Pearsoncorrelation test.Result: The average safe concentration value in this study was 1.1088 mg / m3 with an average value ofmalondialdehyde of 7,784 MU and glutathione of 35,655 ?g / L. Pearson correlation test showed the safeconcentration of toluene and malondialdehyde level was p=0.685 (p> 0.05), with relationship between safeconcentrations of toluene and glutathione was p = 0.808 (p <0.05).Conclusion: This study shows that there was no significant relationship between toluene safe concentrationand levels of malondialdehyde and glutathione.